Management of Facilities and Infrastructure of the PMI Competency Test Professional Certification Institute of East Jakarta Branch - Farah Putri Arijani; Sugiarto; Siti Zulaikha (South Sulawesi Education Development (SSED), 2024)
Competent human resources (HR) are one of the main pillars that build the competitiveness of a nation. Quality human resources that are able to answer future needs. In Indonesia, the rules regarding compulsory education and national education are contained in Law of the Republic of Indonesia No. 20 of 2003 concerning the national education system. Currently, According to the Indonesian Red Cross Professional Certification Institute, there were only 224 certified people from a total of 8274 staff and 45,685 volunteers. Answering these needs, Professional Certification Institutions are needed for Competency Test Sites. it turns out that many Branch/Regency PMIs have not established/formed Professional Certification Bodies due to limited facilities and infrastructure to meet the standards for the establishment of Competency Test Sites in accordance with BNSP Guidelines.The research design used in this study is a qualitative descriptive research to find facts and interpret about